Analysis of the Relationship between the Highest Price and the Trading Volume of the Energy Company Shares in Kazakhstan with Frequency Domain Causality Method - Mashirova, Tazhikul; Tastanbekova, Karlygash; Nurgabylov, Murat; Lukhmanova, Gulnar; Myrzabekkyzy, Kundyz (International Journal of Energy Economics and Policy, 2023)
This study analyzes the causal relationship between the highest price formation and trading volume in Energy Company stocks traded on KASE. In addition, Granger causality analysis is strengthened with frequency domain causality analysis to determine the concentration points of the causality relationship. This aspect provides vital decision support, especially in investment decisions. Three different relationships are identified for the causality between the highest price formation and the transaction volume. There is a two-way causality relationship for KEGC and a one-way for KZTO. No causal relationship was found for KZAP. These results can be interpreted as an indication that the Kazakhstan stock market offers a rich portfolio for investors. The causality structure of the investment climate in Kazakhstan can be analyzed by similar studies on the composite index and other companies traded in KASE. The time interval of the study was determined as between 01.01.2021 and 31.01.2023 and the data used were retrieved from the investing.com website.